Estimating the trade and welfare effects of Brexit: A panel data structural gravity model - Harald Oberhofer; Michael Pfaffermayr (FIW - Research Centre International Economics, 2018)
This paper proposes a new panel data structural gravity approach for estimating the trade and welfare effects of Brexit. The suggested Constrained Poisson Pseudo Maximum Likelihood Estimator exhibits some useful properties for trade policy analysis and allows to obtain estimates and confidence intervals which are consistent with structural trade theory. Assuming different counterfactual post-Brexit scenarios, our main findings suggest that UKs (EUs) exports of goods to the EU (UK) are likely to decline within a range between 7.2% and 45.7% (5.9% and 38.2%) six years after the Brexit has taken place. For the UK, the negative trade effects are only partially offset by an increase in domestic goods trade and trade with third countries, inducing a decline in UKs real income between 1.4% and 5.7% under the hard Brexit scenario. The estimated welfare effects for the EU are negligible in magnitude and statistically not different from zero.
Keywords: F10; F15; C13; C50; 330; Constrained Poisson Pseudo Maximum Likelihood Estimation; Panel Data; International Trade; Structural Gravity Estimation; Trade Policy; Brexit